The Model of Incremental Public Policy Development Formulation: Experimentalist Governance Approach - Setyawan, Dody; Sumartono; Muluk , M.R. Khairul; Amin , Fadillah (JPAS (Journal of Public Administration Studies), 2024)
This paper presents a new model for policy learning in the policy formulation process, integrating the incremental public policy development formulation model and the experimentalist governance approach. The aim of the new model is to offer a comprehensive and effective approach to addressing complex social problems. The study focuses on the activities and measures implemented by the government to control pandemic period. Through interviews, observations, and document analysis, a comprehensive understanding of the pandemic situation was achieved. The use of triangulation adds validity to the research findings, resulting in a well-rounded and reliable analysis of the crisis in the city. The results and discussion demonstrate the effectiveness of the Incremental Public Policy approach, specifically the Adjusted Plagiarism Incremental model, in responding quickly to dynamic situations such as a global pandemic. This model highlights the importance of making incremental changes to existing policies to adapt to changing circumstances. This approach proved effective in addressing the challenges pandemic peiod. By continuously reassessing and adjusting policies based on new information and feedback, the government successfully mitiged impact on the residents of the city in pandemic period. This flexible and adaptive approach to public policy proved crucial in navigating the uncertainties and complexities of the pandemic, emphasizing the significance of agility and innovation in crisis management.